M2-like tumor-associated macrophages drive vasculogenic mimicry through amplification of IL-6 expression in glioma cells - Zhang, Lin (Oncotarget, 2016)
Vasculogenic mimicry (VM) has offered a new horizon for understanding tumor angiogenesis, but the mechanisms of VM in glioma progression have not been studied explicitly until now. As a significant component of immune infiltration in tumor microenvironment, macrophages have been demonstrated to play an important role in tumor growth and angiogenesis. However, whether macrophages could play a potential key role in glioma VM is still poorly understood. Herein we reported that both VM and CD163(+) cells were associated with WHO grade and reduced patient survival, and VM channel counting was correlated to the number of infiltrated CD163(+) cells in glioma specimens. In vitro studies of glioma cell lines implicated that M2-like macrophages (M2) promoted glioma VM. We found that conditional medium derived from M2 amplified IL-6 expression in glioma cells. Furthermore, our data indicated that IL-6 could promote glioma VM, as blocking IL-6 with neutralizing antibodies abrogated M2-mediated VM enhancement. In addition, the potent PKC inhibitor bisindolylmaleimide I could prevent M2-induced IL-6 upregulation and further inhibited glioma VM facilitation. Taken together, our results suggested that M2-like macrophages drove glioma VM through amplifying IL-6 secretion in glioma cells via PKC pathway.